States' Description of Common Core State Standards to Support Students with Severe Disabilities. (September 2017) - Dukes, Charles; Darling, Sharon M.; Bielskus-Barone, Kristina
A review of State Department of Education and school district websites was conducted to determine how policy related to the Common Core State Standards (CCSS) was communicated to teachers of students with severe disabilities. Four states were selected: California, New York, Illinois, and Pennsylvania. State Department of Education websites and three local school districts within each state were chosen for review using locale codes to ensure representation of city, suburban, and rural districts. A total of 16 websites were analyzed using an original instrument designed to capture information about CCSS implementation efforts. Results indicate that there is little information about students with severe disabilities or instructional/pedagogical guidance for teachers in regard to the CCSS on these sites. Thus, it may be difficult for teachers, based on this sample of websites, to translate standards into educational programming for students.